2008
DOI: 10.1002/nag.690
|View full text |Cite
|
Sign up to set email alerts
|

Implicit integration of a chemo‐plastic constitutive model for partially saturated soils

Abstract: SUMMARYA chemo-plastic constitutive model for partially saturated soils is proposed in this paper based on the existing models developed in Hueckel (Int. J. Numer. Anal. Meth. Geomech. 1997; 21:43-72) and Gallipoli et al. (Geotechnique 2003; 53:123-135). The chemical softening effects due to the increase in contaminant mass concentration are considered based on Hueckel's chemo-plastic model. Gallipoli's model is used to simulate the effects of suction and degree of saturation on mechanical behavior of partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…In implicit schemes, all gradients and functions are estimated at advanced unknown stress states and the solution is achieved by iteration. This group of stress integration schemes include Vaunat et al [142], Borja [10], Hoyos and Arduino [46], Zhang and Zhou [153], and Tamagnini and De Gennaro [130]. They usually do not deal with the non-convex problem by avoiding the transition between saturated and unsaturated states.…”
Section: Finite Element Implementationmentioning
confidence: 97%
“…In implicit schemes, all gradients and functions are estimated at advanced unknown stress states and the solution is achieved by iteration. This group of stress integration schemes include Vaunat et al [142], Borja [10], Hoyos and Arduino [46], Zhang and Zhou [153], and Tamagnini and De Gennaro [130]. They usually do not deal with the non-convex problem by avoiding the transition between saturated and unsaturated states.…”
Section: Finite Element Implementationmentioning
confidence: 97%
“…A trial saturation S r,trial can be written as S r;trial ¼ S r;n þ ΔS r;n (43) As indicated by Hu et al [62], the updated soil hydraulic state {e n + Δe n , s t + Δs t , S e,trial } should be located in the zone bounded by the main drying surfaces S r,d and the main wetting surfaces S r,w . The main wetting/drying surfaces can be calculated by…”
Section: Update Of the Degree Of Saturationmentioning
confidence: 99%
“…An early and important contribution is the work of Simo and Taylor , who proposed a general return‐mapping algorithm, together with a general closest‐point projection method, for rate‐independent elastoplastic constitutive models. On this basis, various implicit integration methods were developed . Vaunat et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A notable example is the study by Vaunat et al , who integrated the constitutive equations of the BBM through an implicit scheme able to cope with suction‐induced plastic strains. Similar schemes have been used in a number of other multiphysical contexts, especially in the presence of highly nonlinear models and non‐mechanical agents . The preference towards explicit or implicit algorithms depends on the balance between the advantages of a simple implementation typical of explicit schemes (which, however, must be combined with error control strategies), against the benefits of unconditional stability and faster convergence rates (often accompanied by the algebraic complexity typical of implicit implementations).…”
Section: Introductionmentioning
confidence: 99%